Effect of Musa acuminata and Tectona grandis Leaves as Packaging Materials on Shelf Life of Local Nigerian Corn Jell-o - Oluwagbenga Oluwasola Adeogun ,; Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2018)
Objective: This study investigated the effect of Musa acuminata and Tectona grandis leaves as packaging materials on the shelf life of local Nigerian corn jell-o. Methods: Fungi were isolated from corn jell-o wrapped separately with leaves of M. acuminata and T. grandis, polyethylene bags and aluminium foil at the interval for 7 days. The proximate analyses were carried out on all packaging materials used to store the corn jell-o at the interval for 7 days. Results: The isolated fungi included Aspergillus flavus, Aspergillus niger, Candida spp. and Trichoderma harzianum. The proximate analyses showed that the leaves of M. acuminata and T. grandis have good preservative potential after 7 days as packaging materials for corn jell-o. The carbohydrates, crude fat and fiber contents of T. grandis were 13.91%, 1.64% and 0.93%, respectively, which were higher than the contents in M. acuminata while the protein, moisture and ash contents of M. acuminata were 3.92%, 79.37%, and 0.92%, respectively and showed more considerable contents than T. grandis. Conclusion: The study was able to attest to the uses of M. acuminata and T. grandis locally for the preservation of food products.